Political Ethics Of The Sultanate Of Buton: Integration Of Sharia And Customary Law In The Leadership System Of Modern Buton Society - Junaid Gazalin; La Ode Ardin Talawa; Razzak Aderista; Andre Setyawan; Aulia Aulia (Indonesian Journal of Innovation Multidisipliner Research, 2026)
This study aims to examine political ethics within the governmental system of the Buton Sultanate, particularly regarding the integration of Islamic law (syara) and customary law (adat) in the leadership system of modern Buton society. This research is motivated by various issues emerging in contemporary political and governmental life, such as the decline of political ethics, the increasing practice of corruption, abuse of power, and the growth of pragmatic politics that prioritize political interests over public welfare. These conditions highlight the importance of revitalizing local wisdom values as a moral foundation for building leadership that is just, ethical, and oriented toward social welfare. This study employs a qualitative method with a library research approach. The research data were obtained from various literary sources, including books, academic journals, historical documents, cultural archives, and previous studies related to the Buton Sultanate, customary law, Islamic law, and the political culture of the Buton community. Data analysis was conducted descriptively and analytically through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the governmental system of the Buton Sultanate possessed a strong foundation of political ethics through the integration of religious values, Islamic law, customary law, and social morality in the administration of governance. This integration is reflected in the philosophy of Sarapatanguna, which consists of the elements of religion (agama), Islamic law (syara), deliberation (bicara), and customary law (sara) as the basis of the socio-political life of the Buton community. Furthermore, the concept of leadership in the Buton political tradition emphasizes morality, spirituality, integrity, and social responsibility, as reflected in the leadership philosophy “Inda-inda mo lipu somanamu syara, inda-inda mo syara somanamu agama,” which places religion and law as the primary foundations of political and governmental life. This study confirms that the political ethical values of the Buton Sultanate remain relevant in modern society and can serve as a source of local wisdom in strengthening political morality, governance, and the development of humane and just leadership in Indonesia, particularly in Southeast Sulawesi.